Trends and dynamics of islamic invesment decision factors: A bibliometric analysis and comprehensive literature review - Munawaroh, Siti Ikmatul; Rahman, Taufiqur (Optimum: Jurnal Ekonomi dan Pembangunan, 2025)
Investment as part of economic development affects macroeconomi indicators, including the level of economic growth as measured by Gross Domestic Product (GDP). Indonesia as a country with an Islamic majority continues to experience an increase in the development of Islamic investment. This shows the strong role of Islamic investment in the formation of Islamic capital market capitalisation which has a major impact in encouraging Indonesia's economic growth. This study aims to map the factors associated with Islamic investment decisions on 829 publications articel in a period of 12 years starting from 2012 to 2023. This research method uses quantitative methods through Vosviewer Bibliometric Analysis and qualitative methods through literature studies. The results showed that 5 clusters with a total of 161 topic. Based on the keywords used, research trends indicate that sharia investment, motivation, and financing are the most frequently occurring terms. The implications of this research can help practitioners to design more effective investment strategies, and provide insight to future researchers in finding research novelty. In addition, for policy makers, this research provides a foundation to develop more effective regulations and policies to support Islamic investment as a driver of economic development.